(3eYQaI CSJNQGL GdJGQjN GdYHQGfi HLOGhdgGs - (3eMeO Hf eMeO Hf CHj GdaJM GdUhaj GdTGaYjs ((3eMehO Hf SdjeGf Hf YHO GdQMef Hf eUWai s)
(3ChdgG (B:s
(3bGd CHh GdaJM GdUhai GdHGH GdNGeS ai GdJGQjN GdYHQGfi GdeTghQ HJGQjN GdNdjaI hJRYe CNHGQ GdjghO Gfg JGQjN COe Ydjg GdSdGe s
(3BNQgG (B:s
(3aEf Hbi eYc TghQ ef GdJGQjN GdYQHi eTghQ eVJ ef GdSfI GdYHQjI GdfGbUI GdJGdjg hgj Sfhf GdeMRhQ GdfGbU hGddg CYde Je s
(3HgG LOGhds
(3HgG fXGe GdJYbjHIs
(3hgh GdHGH GdNGeS ef RjL GdUhais
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdadcs